2011
DOI: 10.1115/1.4003874
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Characteristics and Rotating Stall in Turbine Brake Operation of Pump-Turbines

Abstract: Reversible pump-turbines are versatile in the electricity market since they can be switched between pump and turbine operation within a few minutes. The emphasis on the design of the more sensitive pump flow however often leads to stability problems in no load or turbine brake operation. Unstable characteristics can be responsible for hydraulic system oscillations in these operating points. The cause of the unstable characteristics can be found in the blocking effect of either stationary vortex formation or ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(77 citation statements)
references
References 3 publications
5
72
0
Order By: Relevance
“…Both experimental and numerical studies have revealed complex flow characters in the S-shaped region of pump-turbines. Such vortexes may partially block the flow [7,9,10], or cause stall cells to rotate in the runner channels at 50%-70% of the runner rotation frequency [5,6,8].…”
Section: Scaled Pump-turbine Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Both experimental and numerical studies have revealed complex flow characters in the S-shaped region of pump-turbines. Such vortexes may partially block the flow [7,9,10], or cause stall cells to rotate in the runner channels at 50%-70% of the runner rotation frequency [5,6,8].…”
Section: Scaled Pump-turbine Modelmentioning
confidence: 99%
“…In recent years, both experimental and modelling studies have investigated the unstable flow characteristics of pump-turbines operating in off-design conditions [5][6][7][8][9][10]. Husmatuchi et al [5,6] experimentally investigated pressure fluctuations in the gap between the guide vanes and runner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency components in the pressure fluctuations in pump-turbines usually come from stationary vortex, unsteady vortex and rotating stall [18]. To analyze the type of these low frequency components, a low pass filter was used to obtain the time domain signals.…”
Section: Analysis Of Low-frequency Vorticesmentioning
confidence: 99%
“…Hasmatuchi et al [10,11] experimentally measured the flow characteristics using PIV with a numerical investigation of a scale model pump-turbine model at off-design operating conditions in generating mode. Recent publications such as Widmer et al [12] showed that the S-shaped curve can be traced back to flow recirculation and vortex formation within the runner and the vaneless space between the runner and guide vanes. Zhang and Wang [13] simulated the flow in the S region using commercial software and concluded that many large eddies existed in the vanes and runner which wasted much of the water energy and reduced the turbine output.…”
Section: Introductionmentioning
confidence: 99%